Construção de um Vaccinia vírus recombinante expressando a proteína Tirosina Fosfatase 1B (PTP1B) - Mariana Araújo Costa (2017)
Poxviruses are family of DNA viruses that multiply in the cytoplasm of the cells, these viruses have a broad spectrum of hosts that can infect both vertebrate and invertebrate, for which these viruses co-opt host cell signaling to creating an adequate environment for infection and multiplication. In previous studies, our group verified that Vaccinia virus (VACV) activates the MEK / ERK pathway, inducing accumulation of the transcription factors, such as Egr-1, ATF-2, c-JUN, c-FOS. The stimulation of Egr-1 expression showed to be important for VACV multiplication, and for cell-to-cell spread of enveloped viral particles (EV) of VACV and Cowpox virus (CPXV). One of the hypotheses investigated by our group is the effect of Egr-1 on the spread of EV particles occurs through the regulation of the expression of Protein Tyrosine Phosphatase 1B (PTP1B), another host factor. In this way, the activation of poxvirus-induced Egr-1 leads to the suppression of PTP1B expression, which allows the activation of kinases that are important to polymerize actin tails that transport EV to neighboring uninfected cells. Thus, in order to corroborate this hypothesis, the objective of this study was to create a recombinant VACV in which the expression of PTP1B can be controlled by IPTG. To, evaluate if the assisting role of Egr-1 in the dissemination of VACV is due to the regulation of the expression of phosphatase PTP1B. Insertion of ptp1b gene was done by homologous recombination at the locus of the A56R (hemagglutinin, HA) from VACV strain vT7lacOI, using the transport vector pVOTE.1/PTP1B. After this, recombinant virus selection was performed on BSC-40 and MEF cells ; confirmation and validation of exogenous PTP1B expression was done with Western blotting (WB), sequencing, evaluation of viral fitness, immunofluorescence (IF) and qPCR. The results obtained demonstrate that the expression of IPTG-regulated PTP1B has occurred satisfactorily. Moreover, to corroborate that the expression of PTP1B is regulated by Egr-1, MEF WT and knockouts to egr-1 were infected with vT7lacOI/PTP1B and evaluated for PTP1B expression with WB. Our data demonstrate an accumulation of PTP1B in the absence of Egr-1 during VACV infection, and indicate the increase in PTP1B levels after treatment of IPTG-infected cells. Altogether, a very useful tool was developed to analyze the role of PTP1B accumulation in VACV viral biology. This will enable more detailed investigation of the role of PTP1B in the release of poxvirus EV particles.